Regulatory and Planning Speech Functions Influence on the Senior Preschoolers’ and Junior Schoolchildren’s Voluntary Development - Valentyna Poul; Ostap Bodyk (Психолінгвістика, 2019)
The article is based on the idea of studying the growth of the regulatory role of child’s speech in the activity organization and feasance and the conduct of child’s behavior. According to this idea, the child’s volitional behavior arises with the skills appearance to build speech utterances, when youngster begins to draw up a plan of his/her activity and regulate the process of his/her implementation with their help, i.e., the development of planning and regulatory speech functions is in progress.